Changes of the eye during long-term spaceflight. Review - I. A. Makarov; Y. I. Voronkov (Oftalʹmologiâ)
The review includes the publications of the scientific literature on the eye change during long-term spaceflight. The any eye changes such as visual impairment, hyperopic shift in refraction, changes in the intraocular pressure, increased the intracranial pressure, globe flattening, choroidal folding, optic disc edema, and optic nerve kinking and other changes were reported. The main cause of eye disorders, in all probability, is the increase of the intracranial pressure during long-term spaceflight. The reasons of the increased intracranial pressure are a collection of various factors of adaptation mechanisms in the body to weightless conditions. The leading role in the development of intracranial hypertension takes a redistribution of the body fluids (blood and lymph) in the direction of the head, but the opportunities and the effect of other factors are present. Also the displacement and increase of the internal organs volume of the chest can cause external compression of the jugular veins, increasing the pressure of the blood in them, and as the result to lead to the increase of the intracranial pressure. The role of trigger such mechanisms in the development of the intracranial hypertension in the microgravity environment as anatomical predisposition of the body, race, metabolic changes under the influence of high carbon dioxide content in the different compartments of the station, high sodium intake, the enzyme dysfunction, weight exercises of the astronauts was discussed. However, the pathogenic mechanisms is currently still under investigation. An important role in the study of the adaptation mechanisms is given to research not only before and after the flight, but also during the space flight. The accumulated knowledge and experience about the changes in organs and systems in the conditions of human adaptation to microgravity will help answer many questions related to the implementation of the long spaceflights.